Growth Mindset as a Predictor of Academic Persistence in Secondary School Students - Davilla Fikriyah; Agung Nugraha; Muhammad Muhajirin (Edupotensia Foundation, 2026)
This study aims to describe the general profile of growth mindset among students of MA Persis Sindangkasih. The study employed a quantitative approach and used a descriptive research method. The sample consisted of 90 students from MA Persis Sindangkasih. A non-probability sampling technique was applied, specifically saturated sampling. Saturated sampling is a sampling technique in which all members of the population are included as research participants. The instrument used in this study was the Mindset Measurement Scale. The results indicated that most students demonstrated a growth-oriented mindset, with 51% categorized as having a strong growth mindset and 40% as having a weak growth mindset. Only 8% of students showed a weak fixed mindset, and none were classified as having a strong fixed mindset. The mean score of growth mindset was 71, indicating a relatively good level. Overall, the findings suggest that students generally possess a positive growth mindset, although further reinforcement is still needed